Dairy Business Analysis Project: 2004 Financial Summary - Russell Giesy; L. Ely; Albert de Vries; Brent Broaddus; Chris Vann; A. Bell (EDIS)
This publication is a summary of the financial performance of the dairy farms that participated in 2004. It is intended for general use by dairy farmers, the allied industry, and government and educational professionals. This document is AN161, one of a series of the Animal Science Department, UF/IFAS Extension. Original publication date February 2006.